Revisiting the Concept of Being: A Comparative Analysis of Heidegger and Eastern Philosophical Thought - Tita Rostitawati; Ferlin Anwar; Aminudin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This research aims to revisit the concept of Being(exists) through a comparative approach between MartinHeidegger's philosophy and Eastern philosophicalthought, particularly the Vedanta and Taoist traditions.Heidegger, in his work Being and Time, criticizedWestern metaphysics that forgot the question ofexistence (Seinsfrage) and proposed an existentialunderstanding of Being through Dasein's concept. Incontrast, Eastern thought has traditionally emphasized the non-dualistic and intuitive dimensions of existence,as reflected in the concept of Brahman in Vedanta and Dao in Taoism. This study uses the qualitative literature review method with a philosophical hermeneutic approach to examine the ontological and epistemological structures in both traditions. The results of the analysis show that despite coming from different cultural and linguistic contexts, Heidegger and Eastern thought share similarities in criticizing the objectification of reality and emphasizing the subject's existential involvement in uncovering the meaning of Being. These findings open up spaces for dialogue across philosophical traditions and offer an alternative perspective to a more holistic and transcendent ontological understanding.